5G/NGPON Evolution and Convergence: Developing on Spatial Multiplexing of Optical Fiber Links for 5G Infrastructures. Issue 1 (2nd January 2020) - Lagkas, Thomas; Klonidis, Dimitrios; Sarigiannidis, Panagiotis; Tomkos, Ioannis
ABSTRACT: The offering of demanding telecommunication services as promised by the 5G specifications raise the necessity for high capacity, flexible, adaptive, and power conserving fronthaul. Toward this goal, the role of the passive optical network which is responsible for interconnecting the central office (CO) with the cell-sites is crucial. Among the latest related technologies that need to be integrated in the context of the next generation passive optical networks (NGPONs), the most promising for increasing the provided bandwidth, is the optical spatial multiplexing. In this paper, we present the key 5G technologies, focusing on spatial division multiplexing, which constitutes the main innovation of the blueSPACE 5G Infrastructure Public Private Partnership (5G PPP) project. Exploiting the recent developments on multicore fibers (MCFs), optical beamforming networks (OBFNs), analog radio over fiber (ARoF), and spatial-spectral resources granularity in the context of Spectrally Spatially Flexible Optical Networks (SS-FONs), we describe a complete approach for the 5G fronthaul, emphasizing on the efficient allocation of optical resources while aiming at minimizing energy consumption. The modeled optimization problem is thoroughly presented, and the introduced scheme is evaluated through a real-world based simulation scenario, exhibiting quite promising results.